Laparoscopic approach for hepatocellular carcinoma: where is the limit? - Ettorre, Giuseppe Maria; Levi Sandri, Giovanni Battista (Chinese Journal of Cancer Research; Vol 26, No 3 (June 01, 2014): Chinese Journal of Cancer Research, 2014)
Hepatocellular cancer (HCC) is the sixth most common malignant tumor worldwide and the most common primary liver cancer (1). Liver resection or liver transplantation is the therapeutic gold standards in patient with HCC. Due to advanced disease, extrahepatic metastases, or inadequate liver reserve, only 15% to 30% of patients with HCC can undergo to surgery (2). Five-year risk of recurrence of HCC after resection is as high as 70% because the underlying chronic liver disease continues to put the patient at risk for the development of new cancer nodules (3). Starting from the assumption that recurrence may be newly treated with surgery, laparoscopic approach is recommended, when applicable, for limiting the abdominal adhesions. Since 2000, more than 600 cases of laparoscopic resection for HCC have been reported, with no difference on the oncologic outcomes between open or laparoscopic approach (4). In 2008, the Louisville consensus of experts suggested that the best indications for laparoscopy were solitary lesions less than 5 cm, located in the anterior segments, at a distance from the line of transection, the hepatic hilum, and the vena cava (5). Nowadays, those indications seem to be implemented.